2003
DOI: 10.1021/ja020850+
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Reaction Mechanism for Cocaine Hydrolysis in Human Butyrylcholinesterase

Abstract: Butyrylcholinesterase (BChE)-cocaine binding and the fundamental pathway for BChE-catalyzed hydrolysis of cocaine have been studied by molecular modeling, molecular dynamics (MD) simulations, and ab initio calculations. Modeling and simulations indicate that the structures of the prereactive BChE/substrate complexes for (-)-cocaine and (+)-cocaine are all similar to that of the corresponding prereactive BChE/butyrylcholine (BCh) complex. The overall binding of BChE with (-)-cocaine and (+)-cocaine is also simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
284
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 139 publications
(294 citation statements)
references
References 86 publications
8
284
1
1
Order By: Relevance
“…35 The geometries used in the ESP calculations came from those obtained from previous ab initio reaction coordinate calculations. 19 The charges of the atoms of the oxyanion hole and catalytic triad remain the same with those available in Amber7 package.…”
Section: Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…35 The geometries used in the ESP calculations came from those obtained from previous ab initio reaction coordinate calculations. 19 The charges of the atoms of the oxyanion hole and catalytic triad remain the same with those available in Amber7 package.…”
Section: Simulationmentioning
confidence: 99%
“…24 Therefore, starting from the A328W/Y332A 23 or A328W/ Y332G 24 mutant, the rational design of further mutation(s) to improve the catalytic efficiency of BChE against (-)-cocaine can aim to decrease the free energy barrier for the first reaction step without significantly affecting the ES formation and other chemical reaction steps. The analysis of previous experimental and computational data available in literature 19,23,27 clearly shows that the rate-determining step of (-)-cocaine hydrolysis catalyzed by the A328W/Y332A mutant is the first step of the chemical reaction process. Thus, the modeling of the transitional state of this first reaction step (TS1, see Scheme 1) is important for rational design of highactivity mutants of BChE.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…41 , 42 , 43 , 44 ,45 This mechanistic hypothesis has been supported by reported reaction coordinate calculations using the first-principles quantum mechanics (QM) and hybrid quantum mechanics and molecular mechanics (QM/ MM) methods. 38,46 Based on the QM and QM/MM reaction coordinate calculations, the first step of the chemical reaction process is initialized by S198 O γ attack at the carbonyl carbon of the cocaine benzoyl ester to form the first tetrahedral intermediate (INT1) through the first transition state (TS1). Fig.…”
Section: Catalytic Mechanism For Bche-catalyzed Hydrolysis Of Cocainementioning
confidence: 99%
“…A detailed analysis38 , 47 of the MD-simulated structures of wild-type BChE binding with (−)-cocaine and (+)-cocaine revealed that Y332 is a key residue hindering the structural change from the non-prereactive BChE-(−)-cocaine complex to the prereactive BChE-(−)-cocaine complex.38 , 47 A number of possible mutants of BChE were proposed for in vitro experimental tests. 38,47,48, 49 , 50 , 51 ,52 The earliest design of BChE mutants was only based on the modeled or simulated structure of the non-prereactive BChE-(−)-cocaine complex with wild-type BChE; the possible dynamics of the proposed BChE mutants were not examined. Some of the proposed mutants indeed have a significantly improved catalytic efficiency against (−)-cocaine, 38, 47 -52 e.g.…”
Section: Catalytic Mechanism For Bche-catalyzed Hydrolysis Of Cocainementioning
confidence: 99%